2017
DOI: 10.1038/s41561-017-0010-7
|View full text |Cite
|
Sign up to set email alerts
|

Fossil intermediate-depth earthquakes in subducting slabs linked to differential stress release

Abstract: The cause of intermediate-depth (50–300 km) seismicity in subduction zones is uncertain. It is typically attributed either to rock embrittlement associated with fluid pressurization, or to thermal runaway instabilities. Here we document glassy pseudotachylyte fault rocks—the products of frictional melting during coseismic faulting—in the Lanzo Massif ophiolite in the Italian Western Alps. These pseudotachylytes formed at subduction-zone depths of 60–70 km in poorly hydrated to dry oceanic gabbro and mantle per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 49 publications
5
61
0
Order By: Relevance
“…The thin fault vein network of the damage zone was turned into micrometric shear zones producing a well‐sintered ultrafine‐grained texture undistinguishable from textures that would result from intense grain size reduction in solid‐state ultramylonites. We therefore refer to them as “ultramylonite‐like veins.” Similar crystalline aggregates have recently been described in another mantle pseudotachylyte in Lanzo (Scambelluri et al, ). Even if we describe in this study how melting is involved in the formation of these veins, we show that it ends with a final solid‐state viscous flow, which could be referred to as “late coseismic” or “early postseismic” creep depending on the scale at which the sliding evolution is described.…”
Section: Field and Microstructural Observationssupporting
confidence: 84%
See 2 more Smart Citations
“…The thin fault vein network of the damage zone was turned into micrometric shear zones producing a well‐sintered ultrafine‐grained texture undistinguishable from textures that would result from intense grain size reduction in solid‐state ultramylonites. We therefore refer to them as “ultramylonite‐like veins.” Similar crystalline aggregates have recently been described in another mantle pseudotachylyte in Lanzo (Scambelluri et al, ). Even if we describe in this study how melting is involved in the formation of these veins, we show that it ends with a final solid‐state viscous flow, which could be referred to as “late coseismic” or “early postseismic” creep depending on the scale at which the sliding evolution is described.…”
Section: Field and Microstructural Observationssupporting
confidence: 84%
“…Recent experimental results show that the dehydration of antigorite even in small amounts can induce the formation of micropseudotachylytes in olivine aggregates (Ferrand et al, ), associated with stress drops on the order of 100 MPa and water‐bearing glass in fractured olivine. A recent field study evidences high differential stress accumulated in dry and strong metabasic rocks as a trigger for intermediate‐depth earthquakes in subduction zone (Scambelluri et al, ), which paradoxically supports the model of Dehydration‐Driven Stress Transfer (Ferrand et al, ). Thus, finding water fossilized in a frozen mantle earthquake, even in small amounts, suggests that hydrous minerals were present somewhere on the fault path and brings into light their possible involvement in the mechanics of earthquakes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The negative to normal to differential times in the lower layer indicates that earthquakes in the lower layer are not associated with anomalous high Vp/Vs or dehydration. Combined with recent experimental results that suggest that thermal runaway could occur in both hydrous and anhydrous minerals (Ohuchi et al, ), our results are consistent with thermal instability for generating intermediate earthquakes, or stress transfer which requires little dehydration (Ferrand et al, ; Scambelluri et al, ), and argue against dehydration embrittlement as the primary mechanism, at least not in the lower layer of double seismic zones.…”
Section: Discussionsupporting
confidence: 90%
“…• Supporting Information S1 • Table S6 • Table S7 • Table S8 • Table S9 • Table S10 • Table S11 • Table S12 • Table S13 • Table S14 • Table S15 To quantitatively assess the imprint of ongoing eclogitization on seismic images, it is important to combine knowledge of how eclogitization alters the seismic properties of the rocks with the geodynamic and structural framework of subduction and collision zones at various scales. It has been shown that dry crustal rocks can remain metastable throughout significant ranges of changing P-T conditions without any signs of ductile deformation or reequilibration of the mineral assemblage (Austrheim, 1987;Jackson et al, 2004;Scambelluri et al, 2017). While some studies suggest that ductile deformation of dry metastable crustal rocks can be facilitated by extreme grain size reduction (Hawemann et al, 2019;Menegon et al, 2017), the introduction of external fluids is acknowledged as the most effective trigger for ductile deformation and eclogitization (e.g., Austrheim, 1987;John & Schenk, 2003).…”
Section: Supporting Informationmentioning
confidence: 99%